An Eco-philosophical Return to Metaphysics and Ontology: Consciousness is Nature’s Nightmare - Carreiro, Jason Manuel (Sapere Aude, 2012)
Abstract: This study revisits certain metaphysical, linguistic and ontological issues that arise from an Ecological and Philosophical approach to our understanding and relationship to nature. By anthropomorphizing nature, how can one genuinely honor nature’s own being? What are the connections between human nature and the environment? Can we control nature or does nature control us? Is there a relation between perception and consciousness? What are the implications of our detachment from nature? These questions will be addressed from a philosophical and literary approach, refraining from proposing an empirical/pragmatic approach for the sake of proposing before claims of human action, a dramatic and necessary shift of paradigm. Resumo: Este estudo revisita certos problemas de origem metafísica, linguística e ontológica, que emergem de uma análise ecológica e filosófica da origem do nosso entendimento e relação com a natureza. Antropomorfizando a natureza, como poderemos honrar o próprio “ser” da natureza? Quais relações estabelecemos entre natureza humana e o meio ambiente? Controlamos a natureza ou ela nos controla? Há relação entre percepção e consciência? Quais são os resultados do nosso distanciamento da natureza? Estas questões serão analisadas sob perspectiva filosófica e literária, distanciando de uma proposta estritamente empírica e pragmática, no intento de, antes do chamado por mais ação humana, propor uma dramática e necessária mudança de paradigma.